Begging and profiting in the Abbasian Poetry – a Comparative Study - Aryan Abdulqader Othman (Zanco Journal of Humanity Sciences)
This paper tackles an important literary genre which is part of the social subjects. This genre deserves to be studied in details mainly for its lightness and for its importance as well. It was a reaction towards the mode of life whereby the Abbasian society lived during the seventh century H. and which itself was the result of the decline of political, economic, and social conditions and of the spread of poverty as well. All these led to the occurrence of a set of uneven habits and ethics such as intrusion and begging in addition to the greed of poets to get more money, bounties, and fame. Consequently, many famous poets like Bashar Bib Burd, Abo Tamam, Albuhtury and Almutanabi started to earn their living so. This phenomenon, however, produced a peculiar literature that was typical to it as far as epistemology and conception are concerned.  Researches called this type the literature of Begging and profiting.